'This is a competition': The relationship between examination pressure and gender violence in primary schools in Kenya. (September 2018) - Vanner, Catherine
Highlights: Examination pressure can contribute to a perpetuation of gender violence in schools. Corporal punishment and public humiliation were used as motivational tools to try to enhance students' examination performance. Efforts to promote gender equality and protect students from sexual violence were undermined to make more time for examination preparation. Peer victimization was enhanced by the culture of competition encouraged through the focus on examination performance. Abstract: This study explores the relationship between gender violence in schools and teaching and learning processes in two case study primary schools in Kirinyaga County, Kenya. For seven months in 2015, the following qualitative methods were used: participant observation, individual teacher interviews, individual art-based student interviews and member-check interviews with teachers and students. Findings indicate that examination pressure can directly and indirectly perpetuate gender violence in schools by using corporal punishment and public humiliation as motivational tools and by diverting resources from efforts to enhance safety and equality to ever more time for exam preparation.